Satellite-based drought assessment in the endorheic basin of Lake Balkhash - Yegizbayeva, Asset; Koshim, Asyma G.; Bekmuhamedov, Nurlan; Aliaskarov, Duman T.; Alimzhanova, Nazira; Aitekeyeva, Nurgul (Frontiers in Environmental Science, 2024)
This study examines the impact of drought in the Lake Balkhash basin over two decades, focusing on its effects on agriculture and water challenges in Central Asia. Using MODIS satellite imagery and the Vegetation Health Index (VHI), we assessed drought conditions from 2000 to 2020. The study used different methods, like probabilistic mapping, trend analysis, and correlation coefficients. These were used to investigate connections with hydrological factors and analyze land use data and the GRACE dataset on water equivalent thickness. The results indicate that approximately 44% of the Balkhash Lake Basin experienced drought during the study period, affecting both Kazakhstan and China. Severe drought episodes occurred in 2000, 2008, 2014, and 2015. Analysis of drought trends revealed diverse patterns, with 23% showing an increase, 17% a decrease, and 60% remaining stable. Correlations between drought and hydrological parameters varied among stations. This research highlights the complex link between drought and hydrological factors in the Balkhash Lake Basin, emphasizing the need for precise water resource management and climate adaptation. Key strategies include proactive monitoring, tailored interventions, and the use of probabilistic drought mapping for improved water supply management. The study contributes valuable insights for sustainable practices in the region, advancing our understanding of drought dynamics and providing a foundation for informed water resource decisions in Central Asia.